Case Report: Long-term complications of subcutaneous ureteral bypass migration in an adult female Papillon - Lee, Boram; Seo, Jeonghyun; Jeong, Soon-Wuk (Frontiers in Veterinary Science, 2025)
A 6-year-old spayed female 4.4-kg Papillon with only the left kidney presented with vomiting. Imaging unveiled ureterolithiasis and hydronephrosis, while serum chemistry displayed elevated creatinine, blood urea nitrogen, and C-reactive protein. Urinalysis revealed bacteria and bacterial phagocytes. After subcutaneous ureteral bypass (SUB) placement, kidney panels were normalized. The nephrostomy and cystostomy catheters had migrated into the renal parenchyma and bladder wall on postoperative day (POD) 212 and 369, respectively. As the migration advanced, they entered the ureter and bladder on POD 369 and 796, respectively. The SUB, excluding the nephrostomy catheter, was removed on POD 930 due to migration, obstruction, and extrusion of the SUB shunting port. On POD 937, creatinine and BUN levels remained normal. By POD 1063, the ureteroliths had disappeared. This case highlights the need for vigilant monitoring of catheter migration as a potential complication following SUB placement. Early identification and timely intervention are essential for reducing morbidity and improving patient outcomes.